La0.75Sr0.25Cr0.5Mn0.5O3 perovskite developed for supercapacitor applications. (December 2020) - Rehman, Zaeem Ur; Raza, Mohsin Ali; Tariq, Ahmed; Chishti, Uzair Naveed; Maqsood, Muhammad Faheem; Lee, Naesung; Awais, Muhammad Huzaifa; Mehdi, Syed Muhammad Zain; Inam, Aqil
Highlights: La0.75 Sr0.25 Cr0.5 Mn0.5 O3 (LSCM) was synthesized by solution combustion method. Lattice parameter a is increased by increasing pH of precursor solution and particle size is decreased. CV analysis revealed that LSCM produced at pH 4 showed maximum specific capacitance of 751 F/g and areal capacitance of 2.9 F/cm 2 . Abstract: This study reports effect of pH of precursor solution on structure, morphology, and electrochemical properties of La0.75 Sr0.25 Cr0.5 Mn0.5 O3 (LSCM) perovskite which is a potential electrode material for supercapacitors. Nanopowder of LSCM was synthesized using metal nitrates and citric acid by solution-combustion method. Development of crystalline phase in as-synthesized powder after calcination was monitored by X-ray diffraction. Particle sizes of as-synthesized powders were analysed by transmission electron microscopy. Synthesized active material (LSCM) along with carbon black and polyvinylidene fluoride was coated on porous Ni foams by vacuum centrifuge mixing to prepare electrodes. Electrochemical characterization of the electrodes was carried out by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and galvanostatic charge discharge (GCD) in 3 M KOH using saturated calomel electrode as reference electrode. These tests revealed that the electrodes prepared from LSCM powder synthesized at pH 4 (LSCM-(pH4)) displayed the highest specific capacitance of 751 F/g at 1 mV/s and an Aerial capacitance of 2.9 F/cm 2 with ca. 5 mg mass loading of the active material. LSCM-(pH4) showed the lowest charge transfer resistance as determined by EIS and 79 % charge retention after 5000 CV cycles at 50 mV/s. Furthermore, LSCM-(pH4) electrodes were tested using Hg/HgO as reference electrode which showed stability of electrodes in a wider potential window of about 0.8 V. LSCM-(pH4) electrode showed maximum SC of 752 F/g at 1 mV/s. Symmetric supercapacitor developed with LSCM (pH4) displayed SC of 179 F/g at 1 mV/s and charge retention of ca. 92 %.